Eisenhower on leadership : - Axelrod, Alan (Jossey-Bass, 2006)
While Osama Bin Laden on Leadership has not yet turned up, it seems every other historical figure has graced the title of a management self-help book. Veteran business writer Axelrod (Patton on Leadership) follows the genre's common pattern, delivering a brief, adulatory biography of his hero before moving chronologically through WWII. Plucking passages from Eisenhower's writings, he offers short homilies on effective management. Readers will learn that they must "Refuse to Consider Failure," "Use Human Resources Wisely," "Preach Simplicity," "Practice Simplicity" and "Look Beyond Ego to Focus on Issues." Learning from mistakes is not one of the messages because, in Axelrod's account, Eisenhower never made one. The author never attempts the incisive analysis that management authorities like Peter Drucker do, but his lessons ring true, and he dispenses them in lively, cheerful prose.